Inflammatory profile of oxidized phospholipids - Bochkov, Valery N. (Thrombosis and Haemostasis, 2007)
Lipid oxidation products and in particular oxidized phospholipids (OxPL) are increasingly recognized as inducers of chronic inflammation characteristic of atherosclerosis. OxPL stimulate production of chemokines and adhesion of monocytes to endothelial cells. However, accumulating data suggest that, in addition to the proatherogenic and proinflammatory effects, OxPL can stimulate antiinflammatory and tissue-protective mechanisms. Thus, depending on the biological situation, OxPL can either stimulate or inhibit inflammation. In this review, the inflammatory properties of OxPL are discussed together with the underlying receptor, signalling and transcriptional mechanisms.
Keywords: Endothelial cells; phospholipids; inflammation